Clinical features of diverse variants of eating disorders in patients with schizophrenia spectrum disorders - L. M. Vasilenko; L. N. Gorobets; A. V. Litvinov; V. S. Bulanov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The aim of the study was to study the clinical and typological features of eating disorders in patients with schizophrenia spectrum disorders.Materials and methods. We studied 136 patients (84 women and 52 men) with schizophrenia spectrum disorders, aged 19 to 58 years, mean age 37.6±9.8 years; the average duration of the disease was 8.6+7.6 years. Criteria for inclusion in the study: age from 18 to 60 years, the presence of disorders of the schizophrenia spectrum, in accordance with the criteria for ICD-10 (F. 20; F. 25), informed consent for participation in the study. Exclusion criteria: organic diseases of the central nervous system, endocrine pathology, severe somatic and gynecological diseases, pregnancy and lactation. The design of the study was open, comparative, non-randomized. The study of patients was carried out once before the start of therapy. Research methods: anamnestic, clinical-psychopathological, psychometric, anthropometric and clinical-statistical.Results: Clinical and endocrine features of the majority of the studied patients were: appetite deviations, varied in nature, intensity and frequency; an increase in body weight of varying degrees, the predominance of the external type of eating disorders, including as part of a mixed type (more than 60% of cases); a high degree of expressiveness of the emotional and restrictive types; a combination of a significant severity of the emotional type with the apathetic nature of affective disorders occurring within the framework of the underlying disease; single-phase variant of the flow of restrictive type. Clinical features in the studied patients with obesity were the stability of disorders and the combination of increased appetite and daily volume of high-calorie nutrition, incorrect family culinary traditions, the prevalence of mixed or external type.Conclusion. The management of patients with schizophrenia spectrum disorders with eating disorders should be comprehensive, together with endocrinologists, therapists, nutritionists. An integrated approach should include: observation and counseling by narrow specialists, recommendations for the normalization of lifestyle, diet, the formation of a low-calorie diet and nutrition stereotype in the patient’s family.